2018
DOI: 10.20533/ijcdse.2042.6364.2018.0456
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Change Pedagogy and Its Effects On Students’ Cognitive Achievement and Interest in Biology

Abstract: This study investigated the efficacy of conceptual change Pedagogy on students' cognitive achievement and interest in biology. Two research questions and two hypotheses guided the study. A non-equivalent, pretestpost-test quasi experimental design was employed. Four secondary schools were randomly selected in Calabar Municipality and Calabar south Local Government Areas, Cross River State. Two schools were randomly assigned to either experimental or control group. The experimental group students were exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
3
0
1
Order By: Relevance
“…Congruent with other results in the literature (Nadelson et al, 2018;Potvin et al, 2020), the results of this research also showed that teaching with the conceptual change model increased conceptual understanding and minimized misconceptions (Akbaş & Gençtürk, 2011;Heddy et al, 2018). However, most of the research available in the literature has been done with students in kindergarten to high school settings (Amponsah & Ochonogor, 2018;Ekon & Edem, 2018;Gates, 2010;McLure et. al., 2020;Santyasa et al, 2018) or on students enrolled in science-major programs at the university (Arthurs, 2019;Arthurs et.…”
Section: Figure 2 Boxplot Showing the Means Of The Conceptual Change ...supporting
confidence: 80%
“…Congruent with other results in the literature (Nadelson et al, 2018;Potvin et al, 2020), the results of this research also showed that teaching with the conceptual change model increased conceptual understanding and minimized misconceptions (Akbaş & Gençtürk, 2011;Heddy et al, 2018). However, most of the research available in the literature has been done with students in kindergarten to high school settings (Amponsah & Ochonogor, 2018;Ekon & Edem, 2018;Gates, 2010;McLure et. al., 2020;Santyasa et al, 2018) or on students enrolled in science-major programs at the university (Arthurs, 2019;Arthurs et.…”
Section: Figure 2 Boxplot Showing the Means Of The Conceptual Change ...supporting
confidence: 80%
“…This CDA approach provides important information related to which concepts need to be studied more deeply and which concepts can be passed according to student needs (Galvin & Simmie, 2015). This departs from the belief that students have their understanding of various kinds of concepts, both from previous levels of education and from experiences possessed by students (Ekon & Edem, 2018;Pekel, 2019). Of course, it is expected that the understanding possessed by students is the correct understanding of the concept, but it does not rule out misconceptions.…”
Section: Introductionmentioning
confidence: 91%
“…Studies focusing on understanding of diffusion and osmosis confirmed that students show a considerable number of misconceptions and difficulties that are resistant to change by traditional teaching methods (Abdullahi, et al, 2021;Ekon & Edem, 2018;Obochi, 2021). Ekon & Edem (2018) pointed many misconceptions about concentration and tonicity and the influence of life forces on diffusion and osmosis among biology students.…”
Section: Misconception In Diffusion and Osmosismentioning
confidence: 99%
“…Studies focusing on understanding of diffusion and osmosis confirmed that students show a considerable number of misconceptions and difficulties that are resistant to change by traditional teaching methods (Abdullahi, et al, 2021;Ekon & Edem, 2018;Obochi, 2021). Ekon & Edem (2018) pointed many misconceptions about concentration and tonicity and the influence of life forces on diffusion and osmosis among biology students. Dogru &Özsevgeç (2018), andIhemedu (2018) conducted a study on the secondary school biology students on their perceived difficulty of isolated biology topics and reported that osmosis and water potential were regarded by students as being among the most difficult biological concepts to understand.…”
Section: Misconception In Diffusion and Osmosismentioning
confidence: 99%